Cimentação Carbonática em Reservatórios Siliciclásticos - O Papel da Dolomita - - KLEIN, CARLA; MIZUSAKI, ANA MARIA PIMENTEL (Pesquisas em Geociências, 2007)
Carbonates are important diagenetic cements in siliciclastic rocks thus important to determine these rocks as hydrocarbon reservoirs. The cement is the material had chemically precipitated partial or totally pore filling, affecting rock values of porosity and permeability. The acknowledgment of diagenetic patterns those are associated to the carbonatic cement precipitation and their impacts in the reservoirs quality can decrease the risks of exploration and exploitation of new reservoirs. Therefore is necessary the knowledge of origin and processes of carbonate cement’s precipitation. These cements have distribution patterns, mineralogy, textures and isotopic compositions which vary spatial and temporally, depending of perform conditions in each diagenetic environment. One of the most important diagenetic cement is dolomite and the dolomite’s group is compound by dolomite and ankerite. These minerals can be differentiated by analytical techniques such as optical petrography, staining techniques, cathodoluminescence, scanning electron microscopy and isotopes. Besides that, dolomite cement shape in a reservoir can display different forms: rhombs, poikilotopic and saddle in a variety of dimensions, pore filling, replacing detrital carbonate grains, concretions, nodules or stratified layers. Primaries calcite and aragonite replaced can promote precipitation of dolomite through increase of temperature and by presence of Mg-being fluids. The main entrance conditions to form dolomitic cement are: (i) alkaline solutions from pre-existence rocks weathering or evaporitc environments; (ii) marine waters; (iii) clay alteration; (iv) CaCO3 polymorphs dissolution; (v) dissolution of bioclasts. An interesting example of dolomitic cementation is the Carmópolis Member of the Muribeca Formation, hydrocarbon reservoir of the Camorim Field (Sergipe-Alagoas Basin, northeastern Brazil).